SOIL EVOLUTION AND ACCUMULATION OF LOESS-LIKE MATERIAL IN THE CHECHEN DEPRESSION, NORTHERN CAUCASUS, RUSSIA - Khokhlova O.S.; Voronin K.V.; Malashev V.Yu.; Golyeva A.A.; Khokhlov A.A. (My University, 2001)
Morphological and biomorphic studies of a soil chronosequence in the Chechen depression of the Northern Caucasus, Russia, indicate soil evolution and plant successions during the second half of the Holocene. The chronosequence consists of palaeosols buried under archaeological monuments dated to >5000, 3800–4000 and 1600–1700 BP and modern surface soils. The palaeosols buried at >5000 and 3800–4000 BP were developed in somewhat warmer and drier climatic conditions compared to those buried at 1600–1700 BP and the modern surface soils. The Late Atlantic period (ca. 5000 yr BP) was characterized by the mean annual air temperature 0.5°C higher and a mean annual precipitation 100 mm per year lower than the present. The transition to the Subboreal period was marked by unstable climatic conditions, and the Subboreal period was cooler and more humid than the Atlantic. Since then, the climate has fluctuated little. Pedogenesis in the last half of the Holocene was accompanied by synchronous accumulation of loess-like material. The Holocene soils of the depression have developed by a “synlithogenic” model of soil formation. Alternating periods of active sedimentation and pedogenesis on a stable land surface occurred in the Late Pleistocene. The studied Holocene soils probably represent one (the present) pedogenic stage in a sequence pedogenic and lithogenic events that affected this region during the Late Quaternary.
Keywords: Holocene; Pleistocene; Quaternary; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Cenozoic::Quaternary; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Четвертичная